2004
DOI: 10.1590/s0037-86822004000300010
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial de populações de triatomíneos (Hemiptera: Reduviidae) em palmeiras da espécie Mauritia flexuosa no Distrito Federal, Brasil

Abstract: RESUMO Para determinar e analisar a distribuição espacial de populações silvestres de triatomíneos no ABSTRACT To determine and analyze the distribution of Triatominae sylvatic populations in the Federal District of Brazil, 150Mauritia flexuosa palm trees were sampled in six veredas of different landscapes (sylvatic, rural and peri-urban)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 24 publications
(12 reference statements)
5
28
0
13
Order By: Relevance
“…Such information is consistent with the reports of Dias et al 18 who also found the triatomine specimens lodging in the Amazon region.…”
Section: Discussionsupporting
confidence: 93%
“…Such information is consistent with the reports of Dias et al 18 who also found the triatomine specimens lodging in the Amazon region.…”
Section: Discussionsupporting
confidence: 93%
“…A amostragem das palmeiras foi feita em quatro veredas, localizadas na Estação Ecológica de Águas Emendadas (15º34'27"S, 47º36'28"W), Reserva Ecológica do IBGE (15º55' 54"S, 47º54'02"W), Colônia Agrícola Rajadinha (15º46' 14"S, 47º38'58"W) e Colônia Agrícola Alphaville -divisa Distrito Federal e Goiás (16º04'05"S, 47º32'39"W). O método de coleta foi o mesmo usado por GURGEL-GONÇALVES et al (2004). As palmeiras foram escaladas e o material presente nas bainhas foliares (matéria orgânica, folhas e ninhos abandonados) foi coletado em sacos plásticos.…”
Section: Methodsunclassified
“…Arecaceae; Cerrado; Rhodniini; Triatominae. Lent, 1954 {Rn}e Psammolestes tertius Lent & Jurberg, 1965 (CARCAVALLO et al 1998, GURGEL-GONÇALVES et al 2004. Porém, a invasão de R. neglectus no peridomicílio e até intradomicílio tem sido observada em Tocantins, Goiás, Minas Gerais, São Paulo e Paraná (BARRETTO 1979, SILVEIRA et al 1984, GARCIA-ZAPATA et al 1985, GUILHERME et al 2001, SILVA et al 2003, geralmente com baixos índices de infecção por Trypanosoma cruzi chagas, 1909, agente etiológico da doença de Chagas.…”
Section: Rhodnius Neglectusunclassified
See 2 more Smart Citations